Time to consider the role of rationalisation in health psychology. (July 2021) - Bonsu, A.; Walker, P.; Edey, J.; Rea, P.; Kaski, D.; Kheradmand, A.; Saman, Y.; Staab, J.P.; Arshad, Q.
Abstract: Objective: The objective of this study was to determine the interaction between psychological factors, belief systems, and engagement around public health initiatives. Study design: We conducted a longitudinal observational study, utilising convenience sampling to examine illness-related perception in the immediate and medium-term stages of the first wave of the SARS-CoV-2 pandemic in the UK. Methods: Weekly questionnaires assessed our primary measure, illness-related perception, using The Health Anxiety Inventory. Other psychological measures included apathy, loneliness, depersonalisation, state anxiety, trait anxiety as well as personality traits. Multiple regressions were performed to determine which psychological factors predicted the variance of health anxiety every week using the enter method. Results: A combination of psychological variables that varied over time and were modulated by external events predicted the evolution of illness-related perception and associated aversion to perceived threat. Conclusion: Our findings highlight how in the face of a public health crisis, psychological factors play a determining role in the synthesis of beliefs as well as guiding human behaviour.